2013
DOI: 10.1039/c3py00246b
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetoxy-phthalimide (NAPI) as a new H-abstracting agent at high temperature: application to the melt functionalization of polyethylene

Abstract: International audienceA new H-abstracting agent, N-acetoxy-phthalimide (NAPI), was designed that cleaves mainly homolytically into acyloxyl and aminyl radicals at 190 degrees C. Melt PE grafting experiments confirmed the H-abstraction efficiency of NAPI. It was also shown that the grafting of maleic anhydride increased and at the same time undesired crosslinking lowered compared to peroxides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…First of all, the effect of the thermolysis of L101 on the polyethylene backbone was studied through linear viscoelastic measurements which allow to monitor even slightly modification of the PE macromolecular architecture after a cross-linking reaction [23,41]. Since peroxide thermolysis is a relatively slow first-order decomposition that controls the rate of subsequent radical reactions [42], cross-linking rates are, therefore, fastest in the early stages.…”
Section: Grafting Of Tempo or Dpaio Onto Pe In Presence Of L101mentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the effect of the thermolysis of L101 on the polyethylene backbone was studied through linear viscoelastic measurements which allow to monitor even slightly modification of the PE macromolecular architecture after a cross-linking reaction [23,41]. Since peroxide thermolysis is a relatively slow first-order decomposition that controls the rate of subsequent radical reactions [42], cross-linking rates are, therefore, fastest in the early stages.…”
Section: Grafting Of Tempo or Dpaio Onto Pe In Presence Of L101mentioning
confidence: 99%
“…the reactions non-selective. As initiator, dialkyl peroxides are most commonly used and the decomposition mechanism involves initial O-O bond homolysis to generate the corresponding alkoxy radicals that can add to the grafting monomer, which would lead to homopolymers as undesired by-products [20][21][22][23][24]. Alkyl radicals formed by decomposition of the primary radicals are known to preferably add to the monomer.…”
Section: Introductionmentioning
confidence: 99%
“…However, a peroxide initiator was still needed to form the PLA macroradicals. N ‐Acetoxy‐phthalimide (NAPI) was proposed as an alternative to conventional peroxides in polyolefin functionalization . Density functional theory calculations showed that thermal degradation of NAPI preferentially led to the formation of α,α′‐dioneaminyl‐based radicals, with very efficient H‐abstraction ability.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory calculations showed that thermal degradation of NAPI preferentially led to the formation of α,α′‐dioneaminyl‐based radicals, with very efficient H‐abstraction ability. In a lower extent, phthalimide‐ N ‐oxyl (PINO) radicals (nitroxide) were also formed and scavenged the macroradicals . In a recent paper, we showed that thermal degradation of NAPI during PLA reactive extrusion could be used to form PLA macroradicals, and to graft some nitroxides (up to 0.24 mol %) onto the PLA backbone, without the use of peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Polyolefins with their annual industrial production exceeding 100 million tons are the most widely used commercial polymers . However, ecological demands have attracted researchers' attention to biodegradable and biobased polymers.…”
Section: Introductionmentioning
confidence: 99%